2015
DOI: 10.1017/s0007114515000963
|View full text |Cite
|
Sign up to set email alerts
|

Eating out is different from eating at home among individuals who occasionally eat out. A cross-sectional study among middle-aged adults from eleven European countries

Abstract: Eating out has been linked to the current obesity epidemic, but the evaluation of the extent to which out of home (OH) dietary intakes are different from those at home (AH) is limited. Data collected among 8849 men and 14 277 women aged 35-64 years from the general population of eleven European countries through 24-h dietary recalls or food diaries were analysed to: (1) compare food consumption OH to those AH; (2) describe the characteristics of substantial OH eaters, defined as those who consumed 25 % or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 38 publications
5
44
1
Order By: Relevance
“…For example some reports indicate that a low meal frequency (2 vs. 5 eating episodes) is associated with obesity; other evidence indicates a strong influence of snacking (many eating episodes over the day). It can be agreed that under some conditions the presence in the food supply of energy-dense foods, access to high-sugar beverages, specific eating habits and attitudes towards the body and foods can exert effects on specific individuals [18,19,20]. Good data exist for particular countries such as Poland [21,22].…”
Section: Nutritional Factors Food and Eatingmentioning
confidence: 99%
“…For example some reports indicate that a low meal frequency (2 vs. 5 eating episodes) is associated with obesity; other evidence indicates a strong influence of snacking (many eating episodes over the day). It can be agreed that under some conditions the presence in the food supply of energy-dense foods, access to high-sugar beverages, specific eating habits and attitudes towards the body and foods can exert effects on specific individuals [18,19,20]. Good data exist for particular countries such as Poland [21,22].…”
Section: Nutritional Factors Food and Eatingmentioning
confidence: 99%
“…Therefore, eating out-of-home foods was assumed to be one of the factors associated with unfavorable dietary intakes among young women living alone. Meanwhile, a previous study showed that frequent out-of-home eaters reported similar dietary intakes out of home and at home, 22 which suggests that the diet consumed by frequent out-of-home eaters may not be differentially influenced by the consumption of out-of-home foods. Therefore, the effect of out-of-home eating on the dietary intakes among young women living alone may be weaker than in those living with their families.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, the consumption of foods prepared OH has been linked to increased energy intake [11], increased body mass index (BMI), among those that consume these foods [12] and prehypertension in young adults [13]. Eating OH has also been associated with a decreased intake of fruits and vegetables [14], high energy density of food [11] and a lower intake of micro-nutrients [15]. Moreover, evidence suggests that there is a strong association between living in areas with increased exposure to fast food and fast food consumption as part of eating OH [16].…”
Section: Introductionmentioning
confidence: 99%